Understanding parental self-medication with antibiotics among parents of different nationalities: a cross-sectional study - Zhongliang Zhou; Dantong Zhao; Huarui Zhang; Chi Shen; Dan Cao; Guanping Liu; Liang Zhu; Yu Fang (BMC, 2021)
Abstract Background There is an increasing trend on the practices of parental self-medication with antibiotics (PSMA) around world, accelerating the antibiotic abuse. This study aims to examine the nationality differences in the practices of PSMA and knowledge, attitudes and practices (KAP) toward antibiotic use, and understand the practices of PSMA among parents of various nationalities in China. Methods A cross-sectional study based on a structured questionnaire survey was conducted in Xi'an, Shaanxi Province, China, from September 2018 to October 2018. A total of 299 respondents participated in. The practices of PSMA (a dichotomous variable) and KAP toward antibiotic use (a continuous variable) served as dependent variables. Participant's nationality was regarded as the independent variable. Binary logistic regression and ordinary least square regression were employed to examine the association between parent's nationality and the practices of PSMA, and KAP toward antibiotic use, respectively. Results 121 (40.88%) Chinese, 100 (33.76%) other Asians and 75 (25.34%) Occidentals were included in final analysis, with a sample size of 296. Chinese were more likely to practice PSMA (OR = 7.070; 95% CI 1.315, 38.01), with worse knowledge (Coef. = − 0.549; 95% CI − 1.021, − 0.078), attitudes (Coef. = − 3.069; 95% CI − 4.182, − 1.956) and practices (Coef. = − 1.976; 95% CI − 3.162, − 0.790) toward antibiotic use, compared to their Occidental counterparts. The main reasons for the practices of PSMA were enough previous medication experience (80.49%) and same ailments with no need to see a doctor (39.02%), with common symptoms such as fever (60.98%) and cough (58.54%). Purchasing antibiotics at pharmacies (92.08%) and using leftover antibiotics (26.83%) were usual approaches. Conclusions The study highlights the gaps in the practices of PSMA and KAP toward antibiotic use among parents of different nationalities. The access to obtain antibiotics from pharmacies reflects the pharmacists' unaware of laws on prescription of antibiotics, fierce competition in the pharmacy market, and the government's lax supervision in China. It suggests the need to improve pharmacists' training, enforce current legislations on pharmacy market regarding the sale of antibiotics, and provide practical and effective educational interventions for residents about antibiotic use.